Generation of ready to use (RTU) products over China based on Landsat series data. Issue 1 (2nd January 2018) - He, Guojin; Zhang, Zhaoming; Jiao, Weili; Long, Tengfei; Peng, Yan; Wang, Guizhou; Yin, Ranyu; Wang, Wei; Zhang, Xiaomei; Liu, Huichan; Cheng, Bo; Xiang, Bo
Abstract: Earth observation community has entered into the era of big data. Family of Landsat sensors have collected massive medium resolution satellite images, which are valuable for long-term land surface monitoring. In order to significantly reduce the magnitude of data processing for remote sensing data users, Landsat-based Ready to Use (RTU) products have been produced. Main RTU products, including orthorectified products, land surface reflectance, land surface temperature, large-area mosaic image, and standard image map products, are described. The resulting Landsat RTU products are hosted on the RSGS earth observation data sharing web site for free download (http://ids.ceode.ac.cn/rtu/ ). These new products will provide consistent, standardized, multi-decadal image data for robust land cover change detection and monitoring across the Earth sciences. In the coming years, CASEarth DataBank system will be constructed, which is an intelligent data service platform for providing not only the RTU products from multi-source satellite data, but also big earth data analysis methods.